Dinner with friends (Theatre Communications Group, L.A. Theatre Works, Dramatists Play Service, 2014)
Four friends, two marriages, one divorce.

Big eyes (2015)
Walter Keane became a worldwide celebrity and talk show fixture in the 1950s after he pioneered the mass production of prints of big-eyed kids, and used his marketing savvy to sell them cheaply. Unfortunately, he claimed to be the artist. That role was played by Margaret, his shy wife. The ruse broke up their marriage and led to a divorce and a dramatic courtroom battle to prove authorship of the paintings.

Chorus: a novel (Counterpoint, Catapult, Recorded Books, Inc., 2022)
For readers of Alice Munro, Elizabeth Strout, and Claire Lombardo, Chorus shepherds seven siblings through two life-altering events—their mother's untimely death, and a shocking teenage pregnancy—that ultimately follow them through their lives as individuals and as a family The seven Shaw siblings have long been haunted by two early and profoundly consequential events. Told in turns from the early twentieth century through the 1950s, each sibling relays their own version of the memories that surround both their mother’s mysterious death and the circumstances of one sister’s scandalous teenage pregnancy. As they move into adulthood, the siblings assume new roles: caretaker to their aging father, addict, enabler, academic, decorated veteran, widow, and mothers and fathers to the next generation.   Entangled in a family knot, the Shaw siblings face divorce, drama, and death while haunted by a mother who was never truly there. Through this lens, they all seek not only to understand how her death shaped their family, but also to illuminate the insoluble nature of the many familial experiences we all encounter—the concept of home, the tenacity that is a family’s love, and the unexpected ways through which healing can occur.   Chorus is a hopeful story of family, of loss and recovery, of complicated relationships forged between brothers and sisters as they move through life together, and of the unlikely forces that first drive them away and then ultimately back home.

44 inch chest (Distributed by Image Entertainment, 2010)
How far would you go to avenge betrayal? Colin Diamond is about to find out in this gritty, provocative thriller. After he breaks down over the dissolution of his marriage, he kidnaps his wife's lover, and his rage pushes him to the brink of murder as his motley crew of buddies urges him to exact brutal revenge.

Marriage story (The Criterion Collection, 2020)
A love story about divorce. A marriage coming apart and a family coming together. Marriage Story is a hilarious and harrowing, sharply observed, and deeply compassionate film from the acclaimed writer-director Noah Baumbach. Adam Driver and Scarlett Johansson deliver tour-de-force performances as Charlie, a charismatic New York theater director wedded to his work, and Nicole, an actor who is ready to change her own life. Their hopes for an amicable divorce fade as they are drawn into a system that pits them against each other and forces them to redefine their relationship and their family. Featuring bravura, finely drawn supporting turns from Alan Alda, Ray Liotta, and Laura Dern-who won an Academy Award for her performance here-as the trio of lawyers who preside over the legal battle, Marriage Story (nominated for six Academy Awards, including best picture) is a work of both intimacy and scope that ultimately invokes hope amid the ruins.

Intolerable cruelty (Universal, 2004)
Explores the comical and complicated relationship between a saavy Los Angeles divorce lawyer and a gold digging Marylin Rexroth, the former wife of one of his clients.

In the Club (BBC Studios, Kanopy Streaming, 2016)
The return of Kay Mellor's warm series follows the relationship dramas of a group of very different new parents who first bonded in a parentcraft class. The story picks up 10 months on, with all the babies born - and in some cases second ones on the way. In storylines packed with secrets, heartbreak, comedy and pathos, life is proving to be just as much of a rollercoaster for these compelling characters as they emerge from the world of pregnancy and into the reality of parenthood.

The past (Sony Pictures Home Entertainment, 2014)
An Iranian man deserts his French wife and two children to return to his homeland. Meanwhile, his wife starts up a new relationship, a reality her husband confronts upon his wife's request for a divorce.

A.C.O.D: adult children of divorce (2014)
Meet Carter. It's been years since his parents' divorce. But now, with the wedding of this younger brother, he must keep mom and dad from annihilating each other all over again. That's when the real surprises start, including a shocking revelation from his childhood "therapist", the arrival of his dad's latest wife, his own commitment issues with his gorgeous girlfriend, and confronting the sexy A.C.O.D. from his past.

Binge box: Gut busters : the 90s (Binge Box, 2019)
Ace Ventura, pet detective: He's the best there is; in fact, he's the only one there is! He's Ace Ventura, pet detective. He goes eyeball to eyeball with a man-eating shark, stakes out the Miami Dolphins, and woos and wows the ladies. Dumb and dumber: Two half wits travel from Rhode Island to Colorado to return a briefcase full of money to a beautiful socialite. During the course of their moronic mission, these indomitable dimwits confound cops, kidnappers, rednecks and anyone unlucky enough to cross their paths. Mrs. Doubtfire: Troubled that he has little access to his children, divorced Daniel Hillard hatches an elaborate plan. With help from his creative brother, he dresses as an older British woman and convinces his ex-wife to hire him as a nanny. "Mrs. Doubtfire" wins over the children and helps Daniel become a better parent--but when both Daniel and his nanny persona must meet different parties at the same restaurant, his secret may be exposed. Tommy boy: Not-too-smart Tommy inherits the family business from his dad, only to find out the company is in ruins. In order to save it, he has to go across the country with his smart-but-annoying business partner. Wayne's world: Wayne is still living at home and does his own public access TV show from the basememnt. A local station decides to hire him and his sidekick Garth to do their show professionally, and Wayne and Garth find that it is no longer the same.
Ace Ventura : pet detective , Dumb and dumber , Mrs. Doubtfire , Tommy boy , Wayne's world.

Film fan favorites: Scarlet Johansson (Binge Box, 2020)
Jojo Rabbit: A World War II satire that follows a lonely German boy named Jojo whose world view is turned upside down when he discovers his single mother is hiding a young Jewish girl in their attic. Aided only by his idiotic imaginary friend, Adolf Hitler, Jojo must confront his blind nationalism. Girl with a pearl earring: 17-year-old Griet must work to support her family, so she becomes a maid in the house of Johannes Vermeer, where she attracts the master painter's attention. He is commissioned to paint Griet, and the result is one of the greatest paintings ever created. Under the skin: An existential, experimental science fiction film with erotic overtones that journeys to the heart of what it means to be human in which an alien in the form of a voluptuous young woman prowls the streets of Scotland in search of isolated lonely and unsuspecting men whom she lures into her otherworldly lair, where they are seduced, stripped of their humanity, and never heard from again.
Marriage story / written and directed by Noah Baumbach ; produced by David Heyman, Noah Baumbach (2019 : 137 min.) , JoJo Rabbit / screenplay by Taika Waititi ; directed by Taika Waititi ; a Taika Waititi film ; produced by Carthew Neal, Taika Waititi, Chelsea Winstanley (2019 : PG13 : 108 min.) , Girl with a pearl earring / produced by Andy Patterson, Anand Tucker ; screenplay by Olivia Hetreed ; directed by Peter Webber (2003 : PG13 : 100 min.) , Under the skin / produced by James Wilson and Nick Wechsler ; written by Walter Campbell, Jonathan Glazer ; directed by Jonathan Glazer (2013 : R : 108 min.).